PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR DALAM UPAYA PERLINDUNGAN KAWASAN SUCI - Made Dwijadhana (Jurnal Arsitektur ARCADE, 2025)
Abstract:  Besakih Temple is the largest temple for Hindus in Bali Province. The problem that often occurs is when Hindu community pujawali carry out prayers from districts/cities in Bali, as well as outside Bali. Thousands of Hindus come every day to pray at Besakih Temple using land transportation such as two-wheeled motorized vehicles, four-wheeled vehicles, buses, trucks and so on, resulting in extraordinary traffic congestion in the temple area Besakih. Parking facilities are inadequate and insufficient for parking motorized vehicles, so many new parking lots have emerged which are not well managed, thus adding to the chaos that occurs in the Besakih Temple area, especially in the Margi Agung area. Based on this, in 2022 one of the Bali Province's priority programs will be the construction of infrastructure for the protection of the Besakih Sacred Area. The aim of this research is to determine the public's perception of infrastructure development in efforts to protect the Besakih Sacred Area. The research method was carried out qualitatively, by descriptively exploring the data obtained both through direct field observation and through literature data related to the Besakih Sacred Area. The results of the research are in the form of community perceptions which will later be useful as consideration for the Bali Provincial Government in implementing similar programs/activities at other temples under the authority of the Bali Provincial Government. Keyword: Perception, Infrastructure, Margi Agung Besakih Abstrak: Pura Besakih merupakan pura terbesar bagi umat Hindu yang berada di Provinsi Bali. Permasalahan yang sering terjadi adalah pada saat pujawali masyarakat umat hindu melaksakanan persembahyangan dari kabupaten/kota di Bali, maupun luar Bali. Ribuan umat Hindu yang datang setiap harinya, untuk melaksanakan persembahyangan ke Pura Besakih dengan menggunakan transportasi darat seperti, kendaraan bermotor roda dua, kendaraan roda empat, bus, truck dan lain sebagainya, mengakibatkan kepadatan lalu lintas yang luar biasa di Kawasan Pura Besakih. Fasilitas parkir yang kurang memadai dan tidak mencukupi untuk parkir kendaraan bermotor, sehingga banyak bermunculan parkir-parkir baru yang tidak terkelola dengan baik sehingga menambah kesemrautan yang terjadi di Kawasan Pura Besakih, terutama pada areal Margi Agung. Berdasarkan hal tersebut, pada tahun 2022 salah satu program prioritas Provinsi Bali yaitu dilaksanakan Pembangunan Infrastrktur Pelindungan Kawasan Suci Besakih. Tujuan penelitian ini untuk mengetahui persepsi masyarakat terhadap pembangunan infrastruktur dalam upaya perlindungan Kawasan Suci Besakih. Metode Penelitian dilakukan dengan kualitatif, dengan mengeksplorasi secara deskriptif data yang diperoleh baik melalui observasi lapangan secara langsung serta melalui data literatur yang berkaitan dengan Kawasan Suci Besakih. Hasil dari penelitian berupa persepsi masyarakat yang nantinya akan bermanfaat sebagai bahan pertimbangan Pemerintah Provinsi Bali dalam melaksanakan program/kegiatan sejenis di pura lainnya yang menjadi Kewenangan Pemerintah Provinsi Bali. Kata kunci: Persepsi, Infrastruktur, Margi Agung Besakih